2014
DOI: 10.1310/tsr21s1-s52
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Stroke Patients’ Awareness of Risk Factors and Readiness to Change Stroke Risk-Related Behaviors in a Randomized Controlled Trial

Abstract: Purpose:To identify the effects of a brief educational intervention on stroke patients' recall and recognition of risk factors and performance of and stage of change for stroke risk-related behaviors. Methods: Sixty-six patients with stroke participated in a multisite randomized controlled trial. The intervention group (n = 35) received a brief education intervention (tailored written stroke information, verbal reinforcement of information for 3 months after discharge, and provision of a telephone number). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…34 Therefore, comprehensive SK concepts may need to include issues over one's entire life course 35 and encompass the epidemiology, risk factors, warning signs, emergency response, symptoms, and treatment/ rehabilitation of stroke, as well as concepts relevant to the long-term care, disability prevention, and health promotion. 36 Because SK covers multidimensional concepts across the continuum of stroke management, the framework proposed by the European Commission has the potential to be the basis for validating current SK tests and developing or refining additional tests. In addition, developing SK tests that appropriately consider different clinical situations relevant to different target populations is essential.…”
Section: Discussionmentioning
confidence: 99%
“…34 Therefore, comprehensive SK concepts may need to include issues over one's entire life course 35 and encompass the epidemiology, risk factors, warning signs, emergency response, symptoms, and treatment/ rehabilitation of stroke, as well as concepts relevant to the long-term care, disability prevention, and health promotion. 36 Because SK covers multidimensional concepts across the continuum of stroke management, the framework proposed by the European Commission has the potential to be the basis for validating current SK tests and developing or refining additional tests. In addition, developing SK tests that appropriately consider different clinical situations relevant to different target populations is essential.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary outcome for people with aphasia will include a 10-item measure of self-reported stroke risk-related behaviors [ 19 ]. Both ideal (for example, taking medication as prescribed) and nonideal behaviors (for example, smoking cigarettes) will be measured with higher scores out of 10 indicating performance of more ideal behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, people with aphasia who have completed the attention control intervention (SSPIP) are hypothesized to have a significantly better score on a stroke risk-related behavior measure [ 19 ] compared to those who receive the Aphasia ASK intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown the application of this type of intervention in people who have suffered a stroke as a means to reduce the risk of secondary stroke [ 26 ]. Educational intervention in this population remains unusual, however, despite being in great demand, due to the lack of information individuals often encounter in their rehabilitation process [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown the application of this type of intervention in people who have suffered a stroke as a means to reduce the risk of secondary stroke [ 26 ]. Educational intervention in this population remains unusual, however, despite being in great demand, due to the lack of information individuals often encounter in their rehabilitation process [ 26 , 27 ]. Therefore, in order to allow for continuity and applicability to the previous rehabilitation treatment received in the hospital, we propose an educational intervention at home for people who have suffered a stroke and who have been discharged to their homes in the 3 months prior to recruitment to the study.…”
Section: Introductionmentioning
confidence: 99%